Effect of TiO2 incorporation on separation performance of pure PES and PES/PVAc blend membranes - Abdullah, M.A. (Trans Tech Publications Ltd, 2018)
In this research work, polyethersulfone (PES) and polyethersulfone/polyvinyl acetate (PES/PVAc) blend were incorporated with 10 wt. of TiO2 nanoparticles to form mixed matrix membranes (MMM). FESEM and TGA were utilized respectively to scrutinize the morphology and thermal stability of the developed membranes. Permeation tests of ideal CO2 and CH4 gases were also conducted to assess the separation performance of resultant membranes. The PES/PVAc/TiO2 polymer blend MMM was found to be the most thermally resistant and has the highest CO2 permeability and CO2/CH4 selectivity as compared to the other membranes. Â© 2018 Trans Tech Publications, Switzerland.